Empowering the potential of local cultural wisdom in the packaging of performing arts: a force for forming community identity in the Kampung Seni Edas Bogor City - Nurjatisari, Trimulyani; Narawati, Tati; Nugraheni, Trianti; Riyadi, Lanang (Institut Seni Indonesia Surakarta, 2023)
Foreign culture has become a significant polemic for today's millennials, leading to a tendency to overlook their nation's identity and the robust cultural potential inherent in their own country. This article seeks to enhance the potential of local cultural wisdom in the packaging of art as a force for shaping community identity. A qualitative approach is employed to provide a detailed and careful description of the art packaging methods in Kampung Seni Edas. Data were collected through interviews, observations, and documentation, with the research conducted in Kampung Seni Edas, Bogor City. Data validity was ensured through source triangulation and informant review techniques. Data analysis utilized interactive techniques involving data reduction, data display, and verification steps. The results underscore the necessity of elevating the potential of local wisdom in Kampung Seni Edas as an alternative model for empowerment and art packaging, contributing to character building and community identity, ultimately facilitating preservation through innovative performing arts. The implication is that the millennial generation needs to recognize, understand, and study culture as an essential achievement that must be embraced by millennials as the successors of the nation.